Effect of yttria content on CMAS resistance of YSZ thermal barrier coatings - WANG Jing; LU Jie; ZHAO Xiaofeng; CHEN Xiaolong; HUANG Yinan; ZHANG Han (Journal of Aeronautical Materials, 2023)
The corrosion behavior and mechanism of environmental sediment（CMAS molten salt）on different YO1.5-doped zirconia coatings（8YSZ, 38YSZ and 55YSZ）sprayed by atmospheric plasma at 1300 ℃ have been systematically studied. The results show that the 8YSZ coating has severe CMAS corrosion. At the matrix/CMAS interface, non-protective C-ZrO2 containing Ca and low Y content is formed by dissolution-reprecipitation, accompanied by obvious grain boundary corrosion. For 38YSZ and 55YSZ coatings containing high YO1.5 doping content, along with the reaction, in addition to spherical C-ZrO2, protective products of apatite and garnet are also formed, which can effectively prevent further erosion of CMAS molten salt. Moreover, 55YSZ coating shows better resistance to CMAS molten salt corrosion than 38YSZ coating. From the optical basicity perspective, the higher the YO1.5 content, the higher the reactivity between coating and CMAS molten salt, the easier it is to generate stable products in CMAS molten salt. From the reaction process analysis, high YO1.5 content can promote Y3+ in CMAS molten salt saturation, and then generate more stable, continuous phase（such as apatite, garnet）, avoid matrix material and CMAS molten salt further contact and reaction, thus improving the corrosion resistance of CMAS.